2019
DOI: 10.1007/s00213-019-05198-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between the activity of the mesolimbic dopaminergic system and the rewarding properties of pregabalin in mouse

Abstract: Pregabalin is a psychoactive drug indicated in the treatment of epilepsy, neuropathic pain and generalized anxiety disorders. Pregabalin acts on different neurotransmission systems by inactivating the alpha2-delta subunit of voltage-gated calcium channels. In light of this pharmacological property, the hypothesis has been raised that pregabalin may regulate the mesolimbic dopamine pathway and thereby display a potential for misuse or abuse as recently observed in humans. Although some preclinical data support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Disproportionate and phasic dopaminergic signal elicitation within the nucleus accumbens (NAc, the terminus of the mesolimbic system) is currently held to comprise the sine qua non of rewarding and addictive drugs or pursuits [47] and forms the cornerstone of modern neurobiology's mechanistic explanation of how dependence and addiction develops/is maintained. Multiple investigations have corroborated a lack of dopaminergic signal alterations in the NAc with the administration of gabapentin and pregabalin [48][49][50][51][52], or elevation only in experimental groups subjected to chronic painful stimulus via surgical ligation of a spinal nerve. Both drugs have also been shown to decrease or even block opioid-induced NAc dopaminergism [53].…”
Section: Mechanism: Inhibition Of (Cca2d-associated?) Mesolimbic Dopamentioning
confidence: 99%
“…Disproportionate and phasic dopaminergic signal elicitation within the nucleus accumbens (NAc, the terminus of the mesolimbic system) is currently held to comprise the sine qua non of rewarding and addictive drugs or pursuits [47] and forms the cornerstone of modern neurobiology's mechanistic explanation of how dependence and addiction develops/is maintained. Multiple investigations have corroborated a lack of dopaminergic signal alterations in the NAc with the administration of gabapentin and pregabalin [48][49][50][51][52], or elevation only in experimental groups subjected to chronic painful stimulus via surgical ligation of a spinal nerve. Both drugs have also been shown to decrease or even block opioid-induced NAc dopaminergism [53].…”
Section: Mechanism: Inhibition Of (Cca2d-associated?) Mesolimbic Dopamentioning
confidence: 99%
“…A later study also in rats [7] challenged these results and found that pregabalin produced the same rewarding effects under painful conditions as under pain-free conditions when given in supratherapeutic doses. In a recent study on mice [8], pregabalin produced a rewarding effect in a conditioned place preference test. In another animal study [9], mice were exposed to a partial sciatic nerve ligation or were in a control group.…”
Section: Introductionmentioning
confidence: 95%
“…The neurobiological mechanism involved in the abuse liability of gabapentinoids has not been yet clearly investigated. The usual increase in the dopamine levels at the mesolimbic brain circuits has not been proved in preclinical studies ( 14 , 15 ). Gabapentinoids have been reported to produce alcohol/gamma hydroxybutyrate (GHB)/benzodiazepine-type effects mixed with euphoria.…”
Section: Introductionmentioning
confidence: 99%